Nanoscopy of Black Phosphorus Degradation. Issue 12 (17th May 2016) - Gamage, Sampath; Li, Zhen; Yakovlev, Vladislav S.; Lewis, Colin; Wang, Han; Cronin, Stephen B.; Abate, Yohannes
Abstract : The first quantification of geometric properties and modeling of the chemical degradation process of black phosphorus (BP) and investigation of the effectiveness of passivation coatings using infrared nanoscopy is reported. Oxidized phosphorus species are chemically identified locally at the onset of degradation by nanoscale spectrosocopic imaging. Modeling of experimental results suggests a strong influence of degraded areas on adjacent BP.